Two-point superstring tree amplitudes using the pure spinor formalism - Sitender Pratap Kashyap (SciPost Physics Core)
We provide a prescription for computing two-point tree-level amplitudes in the pure spinor formalism that provides finite results that agree with the corresponding expression in the field theories. In [J. High Energy Phys. 07, 139 (2019), Phys. Lett. B 800, 135078 (2020)], the same result was discovered in the bosonic strings with indications of generalization to superstrings in the Ramond-Neveu-Schwarz formalism. Pure spinor formalism is the unique super-Poincare covariant approach to quantizing superstrings [J. High Energy Phys. 04, 018 (2000)]. Since the pure spinor formalism is equivalent to other superstring formalisms, it verifies the above claim. We introduce a mostly BRST exact operator to achieve this.